Sedimentary Provenance Changes Constrain the Eocene Initial Uplift of the Central Pamir, NW Tibetan Plateau - Wang, Ping; Liu, Dongliang; Li, Haibing; Chevalier, Marie-Luce; Wang, Yadong; Pan, Jiawei; Zheng, Yong; Ge, Chenglong; Bai, Mingkun; Wang, Shiguang (Frontiers in Earth Science, 2021)
The Pamir Plateau region of the Northwestern Tibetan Plateau forms a prominent tectonic salient, separating the Tajik and Tarim basins. However, the topographic evolution of the Pamir Plateau remains elusive, despite the key role this region played in the retreat of the Paratethys Ocean and in aridification across Central Asia. Therefore, the SW Tarim and Tajik basins are prime locations to decipher the geological history of the Pamir Plateau. Here, we present detrital zircon U/Pb and apatite fission-track (DAFT) ages from the Keliyang section of the SW Tarim Basin. DAFT ages show that sediments had three components during the Late Cretaceous and two components since the Oligocene. Detrital zircon U/Pb ages mainly cluster between 400–500 Ma during the Late Cretaceous, and coincide with ages of the Songpan-Ganzi and the West Kunlun Mountains. In contrast, detrital zircon U/Pb ages in the Eocene sediments are centered at around 200–300 Ma and 40–70 Ma, with a peak at ~45 Ma, consistent with data from the Central Pamir and the West Kunlun Mountains. The ~45 Ma peak in detrital zircon U/Pb ages since the Eocene indicates a new sedimentary source from the Central Pamir. Non-metric multi-dimensional scaling (MDS) analyses also show that the sedimentary source was closer to the Central Pamir after the Eocene, when compared to the Late Cretaceous. The result shows a clear Eocene provenance change in the Keliyang area. Moreover, this Eocene provenance shift has been detected in previous studies, in both the Tajik and Tarim basins, suggesting that the entire Central Pamir region likely experienced quasi-simultaneous abrupt uplift and paleo-geomorphological changes during the Eocene.